Code-Switching In Ritueli Daeli’s Youtube Playlist: A Content Analysis Of ‘Learning Englishfrom Zero’ Episodes 1–5 - Indana Zulva Wulandari; M. Ridho Kholid; Istiqomah Nur Rahmawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Despite the increasing prevalence of digital educational materials, code-switching as a viable teaching strategy has gained significant traction. This study aimed to identify structural codes of code-switching and their use in communication within the YouTube playlist "Learning English from Zero" by Ritueli Daeli, consisting of episodes 1 to 5. In this study, a qualitative approach employed inductive content analysis with a deductive coding scheme to examine 196 code-switches across a cumulative total of 84 minutes using the frameworks proposed by Poplack (1980) and Appel & Muysken (2006). The study determined that overall, inter-sentential code-switching dominated, with 106 instances (54.08%), while referential code-switching comprised the majority of instances within the discourse, with 104 instances (53.06%), followed by the use of metalinguistic code-switching with 55 instances (28.06%). This study determined that code-switching as an element in teaching can be highly beneficial, particularly for beginners navigating the ESL environment.